2021
DOI: 10.1038/s41396-021-01095-6
|View full text |Cite
|
Sign up to set email alerts
|

Artificial sweeteners stimulate horizontal transfer of extracellular antibiotic resistance genes through natural transformation

Abstract: Antimicrobial resistance has emerged as a global threat to human health. Natural transformation is an important pathway for horizontal gene transfer, which facilitates the dissemination of antibiotic resistance genes (ARGs) among bacteria. Although it is suspected that artificial sweeteners could exert antimicrobial effects, little is known whether artificial sweeteners would also affect horizontal transfer of ARGs via transformation. Here we demonstrate that four commonly used artificial sweeteners (saccharin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 77 publications
4
68
0
2
Order By: Relevance
“… 24 Other dietary elements such as artificial sweeteners have also been shown (in culture) to induce upregulation of conjugation machinery in response to cell stress that may result in increased ARG transfer. 23 Diseases connected to gut inflammation have also been observed to lead to an expansion of the intestinal resistome, including type 2 diabetes, cirrhosis, obesity, and IBD. 7 , 24 , 57 A common mechanism of increased ARG prevalence across these diseases is likely the blooming of ARG-enriched taxa such as the Enterobacterales in response to a dysbiotic state.…”
Section: Environmental and Host Factors Shape The Gut Resistomementioning
confidence: 99%
See 1 more Smart Citation
“… 24 Other dietary elements such as artificial sweeteners have also been shown (in culture) to induce upregulation of conjugation machinery in response to cell stress that may result in increased ARG transfer. 23 Diseases connected to gut inflammation have also been observed to lead to an expansion of the intestinal resistome, including type 2 diabetes, cirrhosis, obesity, and IBD. 7 , 24 , 57 A common mechanism of increased ARG prevalence across these diseases is likely the blooming of ARG-enriched taxa such as the Enterobacterales in response to a dysbiotic state.…”
Section: Environmental and Host Factors Shape The Gut Resistomementioning
confidence: 99%
“… 17 Functional metagenomics directly screens genes for resistance phenotypes and therefore this approach can identify novel ARGs with high specificity, and can be used for the development and augmentation of custom ARG databases. 18 , 19 Through sequence homology to known ARGs, the widespread use of shotgun metagenomics has further enabled detailed analysis of mammalian-associated resistomes across body sites, 20–22 demonstrating that the resistome displays inter-individual variation and correlates with a number of factors further discussed below, including diet, 23 , 24 travel, 25 antibiotic usage, 2 , 22 , 26 , 27 hospital environments, 28 and breastfeeding. 15 , 27 , 29 Yet, determining the clinical relevance of a given ARG presence within the gut microbiome depends not just on its abundance, but also on the relative risks posed by different ARG classes and the frequencies by which they may transmit to pathogens or pathobionts.…”
Section: Introduction: the Constituents Of The Resistomementioning
confidence: 99%
“…Transformation means that extracellular DNA from lysed donor bacteria is taken up by the recipient bacteria and integrated into their genomes so that the recipient bacteria can acquire new traits [ 31 ]. Extracellular DNA is mostly plasmid DNA and fragmented DNA released during active secretion or lysis by bacteria, often carrying ARG [ 32 ].…”
Section: Mechanisms Of the Horizontal Gene Transfermentioning
confidence: 99%
“…The functional enrichment analysis indicated that LPS biosynthesis, flagellar assembly, fimbrial synthesis, bacterial toxin and multidrug resistance were possibly relevant [ 66 ]. Recently, NAS including saccharin, sucralose, aspartame and Ace-K were found to promote the bacterial evolution and horizontal transfer of antibiotic tolerance through natural transformation, resulting in an overexpression of genes encoding DNA uptake and translocation machinery [ 100 , 101 , 102 ]. This finding offers some insights into the roles of NAS in the evolution and dissemination of antibiotic tolerance among bacteria.…”
Section: Artificial Sweetenersmentioning
confidence: 99%